Students’ Reactions to Virtual Geological Field Trip to Baengnyeong Island, South Korea - Woo-Hee Lee; Cheolhong Kim; Heejung Kim; Hee-Soo Kim; Chungwan Lim (ISPRS International Journal of Geo-Information, 2021)
In this study, we evaluated affective components of the learning processes of students after being exposed to a virtual geology field trip of the Baengnyeong Island, South Korea. Changes in students’ cognition of and interest in science and scientific attitude were measured before and after exposure to the virtual field trip. We exposed 106 middle school students to the program and our results revealed that this program had a positive impact on their scientific attitude (p value = 0.014) but no significant changes were observed in the students’ cognition of and interest in science (p value = 0.166). The significant finding from this study was that the VFT program can bring positive scientific attitude as a component of affective learning process. The affective learning process influences the cognitive learning processes and eventually the academic achievement of the students can be improved. In the students’ satisfaction survey, the highest satisfaction level was in the convenience of the program. As access to Baengnyeong Island is limited, though the island is an ideal location for studying geological phenomena, the VFT can be a useful tool for instilling a positive scientific attitude in students via indirect field experience. It can be a good alternative to bridge the education gap between students with special needs who are less mobile and other students.